2009
DOI: 10.1073/pnas.0901369106
|View full text |Cite
|
Sign up to set email alerts
|

Using adult mosquitoes to transfer insecticides to Aedes aegypti larval habitats

Abstract: Vector control is a key means of combating mosquito-borne diseases and the only tool available for tackling the transmission of dengue, a disease for which no vaccine, prophylaxis, or therapeutant currently exists. The most effective mosquito control methods include a variety of insecticidal tools that target adults or juveniles. Their successful implementation depends on impacting the largest proportion of the vector population possible. We demonstrate a control strategy that dramatically improves the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
231
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(255 citation statements)
references
References 33 publications
(39 reference statements)
10
231
2
1
Order By: Relevance
“…Current fumigation methodologies are ineffective, in part because the insecticide dissipates rapidly with no or little residual action (Reiter, 2014). However, there are an increasing number of novel insecticidal techniques that offer potential for more effective vector control (Devine et al, 2009;Ritchie and Devine, 2013). An increased state of alert during a limited time period, made possible through climate-driven dengue forecasts, and rapid implementation of insecticidal methodologies that have residual action offer immense potential to help control dengue epidemics.…”
Section: Resultsmentioning
confidence: 99%
“…Current fumigation methodologies are ineffective, in part because the insecticide dissipates rapidly with no or little residual action (Reiter, 2014). However, there are an increasing number of novel insecticidal techniques that offer potential for more effective vector control (Devine et al, 2009;Ritchie and Devine, 2013). An increased state of alert during a limited time period, made possible through climate-driven dengue forecasts, and rapid implementation of insecticidal methodologies that have residual action offer immense potential to help control dengue epidemics.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies using pyriproxyfen (Sumilarv™ 0.5G [Sumitomo Chemical Co., Osaka, Japan] ) have shown that adult Aedes aegypti mosquitoes contaminated with this IGR can transfer the material to larval habitats. 13 This product could be applied by ULV techniques (as NyGuard™ IGR Concentrate [MGK, Minneapolis, MN] ) to adult mosquito vectors and possibly transferred to larval habitats, significantly increasing efficiency and reducing cost of immature control of RVFV mosquito vectors. The Bacillus thuringiensis israelensis (Bti)-based products have not been used as successfully for RVFV vectors in some situations.…”
Section: Conduct Immature Mosquito Control In Areas At Elevated or Pomentioning
confidence: 99%
“…Recently, several semi-field trials on the control using the horizontal transfer of pyriproxyfen by Ae. aegypti females to their breeding sites were reported to be successful (Shihuincha et al, 2005;Devine et al, 2009). Ohba et al (2011) reported the usefulness of pyriproxyfen-treated net for the control of Aedes albopictus.…”
Section: Effect Of Juvenile Hormone Analogue (Jhm) Pyriproxyfen As mentioning
confidence: 99%